(a+b)+c = a+(b+c) a = 2/9 b = -3/2 c = 1/8 October 10, 2021 by Charlotte (a+b)+c = a+(b+c) a = 2/9 b = -3/2 c = 1/8

Answer: -83/72 = -83/72 So both sides are equal. Step-by-step explanation: (a+b)+c = a+(b+c) (2/9-3/2) + 1/8 = 2/9 + (-3/2 + 1/8) Simplify (2/9 – 3/2) + 1/8 2/9-3/2+1/8 2/9 – 3/2 = -23/18 -23/18 + 1/8 = -83/72 LCM of 72 = 9,2,8 16/72 – 108/72 + 9/72 16 – 108 + 9/72 = -83/72 -83/72 = -83/72 Log in to Reply

Answer:-83/72 = -83/72 So both sides are equal.Step-by-step explanation:(a+b)+c = a+(b+c)

(2/9-3/2) + 1/8 = 2/9 + (-3/2 + 1/8)

Simplify

(2/9 – 3/2) + 1/8

2/9-3/2+1/8

2/9 – 3/2 = -23/18

-23/18 + 1/8 = -83/72

LCM of 72 = 9,2,8

16/72 – 108/72 + 9/72

16 – 108 + 9/72 = -83/72

-83/72 = -83/72